Winning the room : creating and delivering an effective data-driven presentation - Franks, Bill, 1968- (John Wiley & Sons, Inc., 2022)
"This book focuses on common errors that people make when presenting technical data. These errors are magnified when presenting to non-technical audiences. Note that "presenting" in this case applies to both the written/visual presentation one might prepare and to how a person would verbally talk about those written points. While the book will be framed with examples from the analytics and data science space, the points are valid for anyone presenting data and analytics results. The flow of the book will be a series of specific tips. It is anticipated that there will be around 100 tips. Instead of the typical chapter-based format, this book will be broken into sections of general topic areas and then have specific tips within each area. It is anticipated that the topic areas would be of a number such that each has 10 -- 15 tips within it. Given the format, most of the tips will be comprised of just 2 -- 3 pages. Most tips will have a very short (paragraph or two) description of a key point and then a visual of the concept being ignored and a visual of the concept being followed. For example, many people miss simple things like making the number of decimal points consistent across a table. Visually seeing how bad it looks when done wrong will help readers get the point."--